REFERENCE VALUES FOR CEREBRAL OXIMETRY (rSO2) IN CHILDREN AGED 1 MONTH TO 3 YEARS - Кирилл Андреевич Клейменов; Евгения Александровна Каменева; Вадим Гельевич Мозес; Кира Борисовна Мозес; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Евгений Валерьевич Григорьев; Артем Александрович Черных (The Publishing House Medicine and Enlightenment, 2022)
An observational study of cerebral oximetry parameters (rSO2) was performed in 100 children aged from 1 month to 3 years with no history of somatic diseases associated with the broncho-pulmonary system and the central nervous system. Data obtained using Invos 5000C. The index of cerebral oximetry in children of this age group was 63,5 % (60,6:66,6).